2010
DOI: 10.1002/adem.201000123
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Deformation Detwinning—A Reverse Mode of Twinning

Abstract: The deformation mechanisms in crystalline materials, covering metals, alloys, ceramics, and geologic rocks, have to date been well established in the deformation map, which include the dislocation motion in a wide temperature range, grain boundary (GB) sliding at high temperature, and/or twinning at low temperature (LT). Here we report a reverse twinning mechanism-detwinning, which operates at LTs during the tensile deformation of an electrodeposited Cu with a high density of nanosized growth twins. In situ sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…The thickness of twin lamellae containing leading and trailing partials shown in Figure 5(d) is 3.75 nm, increased by a factor of 6 in comparison with the original value of 0.63 nm. Figure 5 reveals that TB migration and subsequent detwinning are originated from the nucleation and subsequent glide of lattice partial dislocations parallel to the twin planes, which is in good agreement with recent experimental studies and atomistic simulations [11,[27][28][29]. …”
Section: Resultssupporting
confidence: 88%
“…The thickness of twin lamellae containing leading and trailing partials shown in Figure 5(d) is 3.75 nm, increased by a factor of 6 in comparison with the original value of 0.63 nm. Figure 5 reveals that TB migration and subsequent detwinning are originated from the nucleation and subsequent glide of lattice partial dislocations parallel to the twin planes, which is in good agreement with recent experimental studies and atomistic simulations [11,[27][28][29]. …”
Section: Resultssupporting
confidence: 88%
“…GBs not only scatter electrons, but can migrate and slide under shear stresses 11 , leading to a maximum in strength in nanocrystalline materials 12,13 . In contrast, such migration/sliding mechanisms may not be operative in CTBs despite some reports of detwinning evidence 7,14,15 and the observation of a similar maximum strength in a nanotwinned copper 3 (nt-Cu). Existing models widely assume perfect CTBs and rationalize flow softening due to CTB migrations and detwinning as caused by nucleation and motion of partial dislocations parallel to CTBs (ref.…”
mentioning
confidence: 97%
“…This scenario is different from the detwinning process through partial dislocation glide proposed by modelling or from the detwinning caused by ITB motions observed in some experiments 17,31 . Nevertheless, the kink-motion proposition has strong implications to the detwinning phenomena observed so far experimentally (for example, detwinning remains active even at low temperatures and often occurs in certain regions) 7,14,15 , as well as a maximum strength seen in nt-Cu (ref.…”
mentioning
confidence: 99%
“…A rigorous investigation performed by Yuan et al [21] clearly demonstrated that the presence of secondary twins could significantly toughen the HNT Cu sample because of crack blunting arising from detwinning of secondary twin lamellae, as well as dislocation emission from the primary and secondary twin boundaries as the secondary twin spacing was small. Inspired by the above findings and in view of the prevalence of detwinning or twin boundary (TB) migration in NT [22][23][24][25] and HNT [19][20][21] metals, an attempt will be made in this letter to develop a theoretical model, by extending the model of Ovid'ko and Sheinerman, [26,27] to investigate the effect of the detwinning behavior on crack blunting in HNT metals. The fracture toughness of the HNT metal with detwinning of the secondary twin lamellae dominating is also discussed.…”
mentioning
confidence: 99%
“…The crack is assumed to nucleate and propagate along the primary TB segment BF, as observed in MD simulations, [21,28] due to the low TB energy. The applied load and the stresses induced at the crack tip are assumed to be sufficiently high (the shear stress is estimated to be around 700 MPa according to existing experimental measurements [24,25]) to initiate detwinning of the secondary twin lamellae ABFE (Figure 1(c) and (d)), which is accompanied by the migration of the secondary TB AB, as observed in the MD simulations. [21] The detwinning process or the TB migration process, which is different from the mechanism of grain boundary (GB) migration, [29][30][31][32] could be achieved by the travelling of the Shockley partials on the TBs, as validated by various experiments [23][24][25] and MD simulations.…”
mentioning
confidence: 99%